EFFORTS TO IMPROVE LEARNING ACTIVITIES AND RESULTS TO WRITE DESCRIPTION PAPER THROUGH THE USE OF SERIOUS IMAGE MEDIA IN GRADE VIIE SEMESTER GASAL STUDENTS OF SMP NEGERI 6 PURWODADI - Sri Sulasih (Literasi Nusantara, 2021)
The use of instructional media in schools is not optimized, causing student motivation and attention when attending lessons is still low. Based on the daily test scores, the grade completeness was only 39%. Therefore, the authors try to overcome these problems by utilizing instructional media, through classroom action research (CAR). This study aims to describe the implementation of learning by utilizing instructional media and to describe the increase in activity and learning outcomes of class VIIE students of SMP Negeri 6 Purwodadi on the subject of analyzing reports. For this reason, this research design uses classroom action research whose activities consist of planning, implementing, observing and reflecting which is divided into two cycles. The subjects of this study were 31 students of class VIIE SMP Negeri 6 Purwodadi in the odd semester of the 2017/2018 school year. The research data were obtained by observation and test methods. The results showed that the use of serial image media in learning could increase student activity and learning outcomes. From the results of the action obtained the average value of student learning outcomes in cycle I 73.32 and cycle II 80.16. This shows that the use of serial image media can improve student learning outcomes.